Relationships between species assemblage richness and acoustic indices - Rojas, Yunevda E. León; Xie, Jie; Colonna, Juan G. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2025)
Biodiversity assessment is increasingly reliant on acoustic indices derived from bioacoustic recordings. This study evaluates the performance of five acoustic indices–Acoustic Richness Index (Hs), Von Neumann Entropy (Hv), Acoustic Diversity Index (ADI), Bioacoustic Index (BIO), and Acoustic Evenness Index (AEI)–in controlled environments. We generated simulated assemblages by randomly mixing vocalizations from distinct species and specimens, creating 24,000 bird assemblages and 2,000 anuran assemblages. Each index was calculated for these datasets to assess its relationship with species richness. The results revealed that these indices exhibited a positive correlation with species richness in the assemblages. However, background noise significantly distorted these correlations. Our findings underscore the need for further research to clarify the specific conditions under which acoustic indices can reliably quantify biodiversity.